CELLULOSE NANOCRYSTALS BASED ON PINEAPPLE LEAF FIBERS IN HEMOPERFUSION APPLICATIONS FOR CREATININE REMOVAL: BATCH METHOD ADSORPTION STUDY - Raharjo, Yanuardi; Darmokoesoemo, Handoko; Fetty, Amelia Julia Tria; Aziz, Rizky Abdul; Salsabila, Fara; Ishma, Ervina Fadhilatul (Jurnal Kimia Riset, 2024)
Kidney failure is a major global cause of mortality, often resulting from the buildup of uremic toxins like creatinine. Creatinine serves as an indicator for assessing treatment needs in kidney failure patients. Hemoperfusion, a treatment based on the adsorption of toxins, has shown promise when using cellulose nanocrystals (CNCs) as adsorbents. CNCs derived from pineapple leaf fibers offer unique advantages due to their abundance of active sites, high adsorption capacity, and strong binding affinity. This study investigates the efficiency of CNCs in reducing creatinine levels, with the reduction attributed to the binding of creatinine to CNC hydroxyl groups. Characterization of CNCs was performed using PSA, XRD, FTIR, and SEM-EDX techniques, while the residual creatinine was quantified via UV-Vis spectrophotometry, utilizing a picric acid complex under alkaline conditions and measured at 485 nm. Optimal conditions were found with a stirring speed of 210 rpm, 120-minute contact time, and 10 mg/L creatinine concentration, resulting in an adsorption capacity (Qads) of 2.572 mg/g. The CNC adsorbent demonstrated hemocompatibility, with an APTT blood coagulation time of 31.3 seconds. These findings suggest that CNCs could be highly effective in developing safer, efficient hemoperfusion systems for managing kidney failure.